2017
DOI: 10.1063/1.4978514
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in Josephson transmission line stimulated by load in the presence of noise

Abstract: The joint action of the matching to a common RC-load and thermal noise on the spectral properties of parallel Josephson junction array is studied. It is demonstrated that proper matching suppresses the chaotic dynamics of the system. The efficiency of radiation is found to be highest within a limited frequency band, which corresponds to transformation of the shuttle soliton oscillating regime into the linear wave resonance synchronization mode. In this frequency band the spectral linewidth agrees well with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…One can see that in the latter case the oscillation power increases and can be observed in a much wider frequency range. Therefore, this experimental result is a confirmation of recent theoretical observation that the oscillation power in the case of lag-synchronization (occurring also in the travelling wave regime) can be several orders of magnitude larger than for perfect in-phase synchronization of chain elements [53]. These results also show the advantages of using long Josephson junctions over short ones to develop an effective THz generator.…”
Section: Resultssupporting
confidence: 88%
“…One can see that in the latter case the oscillation power increases and can be observed in a much wider frequency range. Therefore, this experimental result is a confirmation of recent theoretical observation that the oscillation power in the case of lag-synchronization (occurring also in the travelling wave regime) can be several orders of magnitude larger than for perfect in-phase synchronization of chain elements [53]. These results also show the advantages of using long Josephson junctions over short ones to develop an effective THz generator.…”
Section: Resultssupporting
confidence: 88%
“…One can see that in the latter case the oscillation power increases and can be observed in a much wider frequency range. Therefore, this experimental result is a confirmation of recent theoretical observation that the oscillation power in the case of lag-synchronization (occurring in the travelling wave regime) can be several orders of magnitude larger than for perfect in-phase synchronization of chain elements [52]. These results also show the advantages of using long Josephson junctions over short ones to develop an effective THz generator.…”
Section: V1supporting
confidence: 88%
“…We have shown that the amount of conditioning depends on the type of graph and, along a given “topological” direction, the increase in the gap is uniform over all of the islands: proof of this effect for the rays of a star array has been reported herein. We have reported an observation, to be further developed, of the effects that finite size could have on double-comb structures; the relevance of these type of effects has also been investigated for discrete Josephson structures in the framework of coherent oscillations and radiation generation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%